HAPPINESS INDEX OF CHILI FARMERS IN SUKAU DISTRICT, WEST LAMPUNG REGENCY - Naqiyya Amaniya Thooriq; Nur Ocvanny Amir; Muhammad Zul Mazwan (Universitas Sebelas Maret, 2025)
Measuring the level of farmer welfare can be observed not only from the material aspect but also from the happiness level of the farmer. The happiness indicator can be described as subjective well-being. This study aims to measure the happiness index of chili farmers in Sukau District, West Lampung Regency. The research was conducted in January 2021, and the research location was selected purposively considering that Sukau District is one of the chili-producing centers in West Lampung. This research employs descriptive quantitative research using a case study approach. Samples of 41 chili farmer respondents are selected from a population of 71 chili farmers, calculated using the Taro Yamane formula. Data was collected through interviews with questionnaire tools to calculate the happiness index following BPS methods. The happiness index of BPS consists of 3 dimensions, namely the dimension of life satisfaction, the dimension of feelings, and the dimension of the meaning of life, and consists of 19 indicators. The results obtained from the life satisfaction dimension were 76.5, the meaning of life dimension was 61.4, and the feeling dimension was 79.3. The final result of the happiness index of chili farmers in Sukau District is 72.7, so it can be concluded that chili farmers in Sukau District are happy because the value is above 60.0.